A formação na Licenciatura em Artes/Música da UNIMONTES e suas inter-relações com aspectos socioculturais, expectativas e pretensões profissionais dos estudantes do Curso - Oliveira , Mário André Wanderley (2011)
The contemporary music education has notably expanded its epistemological boundary due to the breadth, depth and multiple facets of its study "object", as well as the breadth, depth and multiple facets of knowledge needed to understand that "object": music teaching and learning. This perspective, which spread and permanent reconstruction offered significant advances in the area over the past 30 years has pointed to the implications of comprehensive understanding about music and education in music teacher education. Thus, questions are emerging such as: How has the process in undergraduate courses in music? How this process has been happening? Who are the students and how they relate to their undergraduate course? Thus, in order to discuss and reflect on these questions, this study sought to understand how Arts / Music Course of UNIMONTES is inter-related with expectations, socio-cultural characteristics and aspirations of its students. To this end, this research made use of the following: literature research, which covered essentially studies of contemporary music education on the national music teacher education, and also the work of ethnomusicology, education, sociology and anthropology, which allowed contributions to the work in analytical and reflective stages; documentary research, which included documents from the Brazilian Ministry of Education, State Board of Education of Minas Gerais and UNIMONTES, relating to the education of music teachers, and the use of questionnaires and semi-structured interviews with the students. Thus it was possible to verify that in the specific case of UNIMONTES, the education of music teachers shows in his idealized plan, designs and plans in line with current legislation and with the current literature on music teacher education. However, when analyzing the curriculum proposed in the undergraduate project, it was checked some distance from what is presented in other parts of the document. Based on the perspectives that students had about themselves and relationships they have with the education of music teacher offered, the course in question does not seem to suffer great influence of the characteristics of university students and some of the (s) field (s) of work that they aim to act. But students seem to fit the course, lining up for what is offered. Through the perspectives that change during the education process, undergraduates seem to envision new possibilities for action – such as teaching in higher education coupled with research, the main object of desire of most students. Upon completion of this work, carried out in the light of contemporary studies, some reflections emerged, and almost all are related to the question: Are the concepts that guide the education for music teacher at the university are aligned with the concepts that are expected to be present in the work of theses future professionals?